Who represents me? A patient‐derived model of patient engagement via patient and family advisory councils (PFACs) - Vadim Dukhanin; Scott Feeser; Scott A. Berkowitz; Matthew DeCamp (Health Expectations, 2020)
Abstract Background Despite increasing attention to patient and family advisory councils (PFACs), what patients who are not PFAC members expect of PFACs remains understudied. Understanding their expectations is critical if PFACs are to help health systems achieve certain outcomes (eg increased patient satisfaction with health systems). Objective To obtain rich insights about what patients who are not PFAC members expect of PFACs. Design From July to September 2018, we conducted a qualitative study using focus groups. Setting and participants We recruited patients and caregivers who receive their care from the Johns Hopkins Medicine Alliance for Patients (JMAP), LLC, a Medicare accountable care organization that in 2014 established a PFAC, the Beneficiary Advisory Council. Approach Using grounded theory, we analysed field notes, analytic memos and transcripts to develop a theoretical model of patient engagement via PFACs. Results Forty‐two patients and caregivers participated in five focus groups that included individuals of different ages, races, health statuses and socio‐economic statuses. Participants were largely unaware of PFACs. Participants wanted to know who represented them (interpreted as a form of political representation) and emphasized the need for representatives’ diversity. Who mattered because who could affect what PFACs do. Participants expected that all patients should be able to communicate with PFACs and that meaningful engagement could enhance perceptions of health systems. Conclusions Eliciting views about patient representation from patients who have not been engaged as advisors or representatives has the potential to inform PFACs’ activities. Attention should be given to improving and measuring patients’ awareness of, and interactions with, their patient representatives.